TERHADAP KUALITAS ORGANOLEPTIK PUDING RUMPUT LAUT (Eucheuma cottonii) - Rosalita, Rosalita; Syam, Husain; Fadilah, Ratnawaty (Universitas Negeri Makassar, 2018)
This study aims to determine the effect of immersion with orange acid and rice water to organoleptic quality of seaweed pudding (Euchema cottonii). Testing include organoleptics, determining moisture content, ammonia, proteins, carbohydrates and ash levels content contained in seaweed pudding. The research method used Randomized Complete Design (RAL) of 9 treatments and 3 repetitions. The results showed that for the color, taste, aroma, texture most preferred by panelists with was long immersion 36 hours, with the value of each of the color of 5,56%, 5,59% aroma, flavor 5,56 % and texture 5,86%. Treatment was long immersion 36 hours with orange acid has ammonia content 0,003%, water content 84,4%, protein content 0,111%, carbohydrate content 13,063% and ash content 9,62%.